PENGARUH KUALITAS LAYANAN, RISIKO YANG DIRASAKAN, KEPERCAYAAN TERHADAP NIAT PERILAKU UNTUK MENGGUNAKAN APLIKASI BRIMO - Fhaif Yusron Afdillah; Mahmud Mahmud (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The purpose of the research was to determine the effect of service quality, perceived risk and trust on customers' interest in using the BRIMO application. This study uses a quantitative research design. Data obtained from distributing online questionnaires with Google Form. The sampling technique used is a purposive sampling technique. The number of samples used amounted to 100 respondents. In this study several tests were carried out such as validity tests, reliability tests, classic assumption tests, t-tests and F-tests with a significance value of 0.05. The results of the study prove that partially, the variables of service quality and trust have a positive effect on the intention to use the application, while perceived risk has a negative effect on the intention to use the application.